MACT/UFSM: percurso de um museu universitário em arte-ciência-tecnologia - Callero, Juliana dos Santos (2024)
This research investigates the path of the Museum of Art Science Technology of the Federal University of Santa Maria, MACT/UFSM, based on an analysis of its projects and actions, and of the Brazilian university museums that were its foundations: the Museum of Contemporary Art of the University of São Paulo, MAC/USP; and the Museum of Science and Technology of the Pontifical Catholic University of Rio Grande do Sul, MCT/PUCRS. It also aims to recognize how these museum spaces within public and private higher education institutions develop exhibition strategies in the on-site and online environment, such as social networks. To this end, a literature review was carried out, as well as on-site and online field research in the selected museums, and data analysis and discussion using a qualitative approach with an emphasis on Art History, Theory and Criticism. The dissertation instigates discussions on the importance of these university museums as environments that provide teaching, research, extension and cultural innovation experiences, and also favor the integration of the university with the academic and external community. It is hoped that MACT/UFSM will establish itself as a benchmark for transdisciplinary university museums, stimulating the development of theoretical and practical research involving art, science and technology, contributing to new exhibition and museum strategies both on site and online in the context of contemporary art.